A Retrospective Autopsy Based Study On the Pattern of Head Injuries in Pillion Riders Involved in Fatal Road Traffic Accidents. - Sukumar, Sanjay (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Head injury is one of the commonest causes of mortality in motorcycle accidents. This study aims to determine the pattern of injuries in fatal cases of pillion rider accidents, because few studies have been conducted on this topic. Methods: A total of 34 cases of pillion rider fatalities in Pondicherry, India were included in the study. Results: Scalp injuries and fractures were more commonly seen over the occipital (41% and 47%, respectively) and temporal region (21% and 38%, respectively) of the head especially in females, also slip and fall off motorcycle (38%) was the commonest mode of injury. Conclusion: Slip and fall was significantly higher (92%) in females as the position adopted by female pillion riders was usually the side saddle position and the impact part of the head, in falls from this position, usually involves the occipital or temporal region of the head. To prevent the slip and fall off the bike, a safety belt/harness can be used to control the fall of the pillion rider seated in a side saddle position, and this could reduce the mortality and morbidity in pillion riders to some extent.